PENGEMBANGAN BIG BOOK BERBASIS MODEL PAIRED STORY TELLING PADA MATERI BAHASA INGGRIS - A.R, Christi Parnamita; Rufi’i , Rufi’i; Sitompul , Catherine (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop and produce learning products in the form of Big Book media based on the Paired Story Telling model on valid, practical, and effective English material. This development research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) design. The subjects of the study were 26 students of grade 5 of SDN Jagalan 5 Kediri. The data collection instruments used included: (1) student response questionnaires to measure the practicality of the media, (2) validation questionnaires for material experts and design experts to assess the validity of the media, and (3) learning outcome tests to measure the effectiveness of the media. The results of the analysis of the student response questionnaire showed that the Big Book media obtained a validity score of 90% with the category